Hubungan Kekuatan Otot Lengan dan Koordinasi Mata-Tangan dengan Kemampuan Passing Atas Pemain Bolavoli Ganesta Kabupaten 50 Kota - Nofindra, Genta (LITPAM, 2026)
Penelitian ini bertujuan untuk mengetahui hubungan kekuatan otot lengan dan koordinasi mata-tangan dengan kemampuan passing atas pemain bolavoli Ganesta Kabupaten 50 Kota. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Sampel penelitian berjumlah 20 pemain inti putra yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan tes push up untuk kekuatan otot lengan, tes lempar tangkap bola tenis untuk koordinasi mata-tangan, dan tes passing atas untuk mengukur kemampuan teknik. Analisis data menggunakan uji normalitas Liliefors, korelasi Pearson Product Moment, dan korelasi ganda. Hasil penelitian menunjukkan terdapat hubungan signifikan antara kekuatan otot lengan dengan passing atas (r=0,767; kontribusi 58,83%), koordinasi mata-tangan dengan passing atas (r=0,71; kontribusi 50,41%), serta hubungan simultan kekuatan otot lengan dan koordinasi mata-tangan dengan passing atas (r=0,913; kontribusi 83,36%). Temuan ini menunjukkan bahwa peningkatan kualitas passing atas tidak hanya dipengaruhi aspek teknik, tetapi juga kemampuan fisik dan koordinasi neuromotorik pemain. Overhead passing performance among regional-club volleyball players has received limited attention when upper-limb physical capacity and visual-motor coordination are examined simultaneously, as prior studies have largely focused on school or developmental-athlete populations. This study examined the partial and combined relationships of upper-limb muscular endurance and hand-eye coordination with overhead passing ability among Ganesta volleyball players in Lima Puluh Kota Regency. A quantitative correlational design was used with 20 male core players purposively selected from a population of 30 players. Upper-limb muscular endurance was assessed using a one-minute push-up test, hand-eye coordination using a tennis-ball wall throw-and-catch test, and overhead passing ability using a wall passing test. Data were analyzed using the Liliefors normality test, Pearson product-moment correlation, correlation significance tests, and multiple correlation at α=0.05. Upper-limb muscular endurance was positively associated with overhead passing ability (r=0.767, t=5.07, p<0.001, R²=58.83%), as was hand-eye coordination (r=0.710, t=4.28, p<0.001, R²=50.41%). Jointly, both predictors showed a very strong association with overhead passing ability (R=0.913, F=42.57, p<0.001, R²=83.36%). These findings indicate a strong linkage between repeated upper-limb physical capacity, visual-motor coordination, and overhead passing performance in the studied sample. Because the sample was small, male-only, and drawn from one club, the findings should be generalized cautiously and should not be interpreted causally.